2016
DOI: 10.1016/j.celrep.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive RNA Polymerase II Interactomes Reveal Distinct and Varied Roles for Each Phospho-CTD Residue

Abstract: Summary Transcription controls splicing and other gene regulatory processes, yet mechanisms remain obscure due to our fragmented knowledge of the molecular connections between the dynamically phosphorylated RNA polymerase II (Pol II) C-terminal domain (CTD) and regulatory factors. By systematically isolating phosphorylation states of the CTD heptapeptide repeat (Y1S2P3T4S5P6S7), we identify hundreds of protein factors that are differentially enriched, revealing unappreciated connections between the Pol II CTD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
177
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(198 citation statements)
references
References 50 publications
(93 reference statements)
20
177
1
Order By: Relevance
“…On average, each CTD heptad is phosphorylated once and the occurrence of two phosphorylations per repeat is a rare event (13,14). The coimmunoprecipitation of specific CTD phosphoisoforms revealed distinct functional sets of factors (CTDinteractome) related to each CTD phosphoisoform (15).…”
mentioning
confidence: 99%
“…On average, each CTD heptad is phosphorylated once and the occurrence of two phosphorylations per repeat is a rare event (13,14). The coimmunoprecipitation of specific CTD phosphoisoforms revealed distinct functional sets of factors (CTDinteractome) related to each CTD phosphoisoform (15).…”
mentioning
confidence: 99%
“…S5P is required for efficient co-transcriptional splicing and has been reported to be involved in spliceosome assembly at the 5 0 and 3 0 splice sites triggering a splicing checkpoint and RNAPII pausing at intron-exon junctions. [15][16][17][29][30][31] Mammalian NET-seq demonstrated RNAPII S5P enrichment at 5 0 and 3 0 splice sites 15 and phospho-specific RNAPII immunoprecipitations have revealed that RNAPII S5P interacts with key proteins involved spliceosomal assembly. 15,16,29 For a detailed reviews on co-transcriptional splicing, we refer the reader to Saldi et al (2016) and Jonkers et al (2015) 25,32 .…”
Section: Splicing Checkpointmentioning
confidence: 99%
“…[15][16][17][29][30][31] Mammalian NET-seq demonstrated RNAPII S5P enrichment at 5 0 and 3 0 splice sites 15 and phospho-specific RNAPII immunoprecipitations have revealed that RNAPII S5P interacts with key proteins involved spliceosomal assembly. 15,16,29 For a detailed reviews on co-transcriptional splicing, we refer the reader to Saldi et al (2016) and Jonkers et al (2015) 25,32 . Spliceosome assembly is a multi-step process that occurs on the pre-mRNA transcript, starting with recruitment of U1 snRNP at the 5 0 splice site 33 and U2 snRNP to the exonic nucleosome at the 3SS 34 and then at the branch point to form the pre-spliceosome (complex A).…”
Section: Splicing Checkpointmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, distinct next-generation sequencing approaches have measured the coupling of transcription to splicing in Saccharomyces cerevisiae: fast metabolic labeling with 4-thio-uracil (4tU-seq) (Barrass et al 2015), nascent RNAseq (Harlen et al 2016), and single molecule intron tracking (SMIT) (Carrillo Oesterreich et al 2016). These approaches produce, for many genes, quantitative estimates of the speed of splicing, extent of cotranscriptional splicing, or polymerase position at splicing, respectively.…”
Section: Introductionmentioning
confidence: 99%